Pengembangan Pemahaman Networking dan Internet Of Thing (IOT) Kepada Siswa-Siswi SMK Plus Al Musyarrofah Jakarta Selatan - Wahyu Joko Saputro; Tutik Lestari; Supriadi Panggabean (Jurnal Pengabdian Masyarakat (Bisma), 2024)
ABSTRACK The development of information and communication technology, especially in the field of computer networks (networking) and the Internet of Things (IoT), is a very important competency for Vocational High School (SMK) students. This Community Service (PkM) activity aims to improve the understanding and skills of SMK Plus Al Musyarrofah students, South Jakarta, in basic networking concepts, simple network configurations, and IoT applications. The training method includes providing theoretical materials, direct practice, and problem-based learning case simulations. The results of this activity show a significant increase in the level of student understanding of network topology, communication protocols, and simple implementation of IoT in everyday life. This activity is expected to be the first step in preparing students to face the needs of industry 4.0.